Aggression from Patients or Next of Kin and Exposure to Bullying Behaviors: A Conglomerate Experience? - Iselin Reknes; Guy Notelaers; Nils Magerøy; Ståle Pallesen; Bjørn Bjorvatn; Bente Elisabeth Moen; Ståle Einarsen (Nursing Research and Practice)
Although workplace violence and aggression have been identified as important stressors in the nursing profession, studies simultaneously comparing patient-initiated aggression and exposure to bullying behaviors at work are rather scarce. The aim of this study was to compare aggression from patients or next of kin and exposure to bullying behaviors in terms of prevalence, health-related quality of life outcomes, and potential overlap in those targeted. In the period of 2008-2009, data were collected among 2059 members of the Norwegian Nurses Organization. Latent class (LC) analysis and a multivariate analysis of variance (MANOVA) were used to investigate the proposed relationships. The results showed that aggression from patients or next of kin and exposure to bullying behaviors were perceived as separate and independent stressors. Although aggression from patients or next of kin was more frequent than workplace bullying, the latter was the only significant stressor related to health-related quality of life in terms of reduced mental health functioning. Although being a rather infrequent experience, exposure to bullying behaviors seems to have more severe health-related outcomes for nurses than aggression from patients or next of kin. Hence, the results of the study strengthen previous findings and suggest that managers must aim to maintain a positive psychosocial work environment with zero-tolerance for bullying.